Evaluasi Strategi Konten Digital Berdasarkan Kinerja Media Sosial Platform Instagram dan Tiktok - Februrita Mia Nur Yulia; Muhammad Syihabbudin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to evaluate the digital content strategies implemented by Company XY, an MSME in the automotive spare parts sector, on Instagram and TikTok platforms, and to analyze the performance of both platforms in terms of reach and audience response. A qualitative case study approach was employed, with data collection techniques including observation, documentation, and interviews with the marketing team and account visitors. The analysis was conducted by referring to digital content strategy elements, social media performance indicators (4C), and the Uses and Gratifications Theory. The results indicate that the implementation of a structured content strategy significantly enhanced social media performance. Entertainment and humor-based content using a soft-selling approach was identified as the most effective format, contributing 75.5% of the total overall metrics. TikTok played an optimal role in reaching new B2C (Business to Consumer) audiences through the FYP (For Your Page) algorithm, while Instagram excelled in building brand credibility and maintaining B2B (Business to Business) customer loyalty through educational product content. Despite the increase in reach, the effectiveness of conversion through vouchers and discounts remained low. Therefore, optimization of incentive strategies and the recruitment of dedicated digital marketing staff are required to enhance interaction and sales volume.